Growth of a deep-water, predatory fish is influenced by the productivity of a boundary current system - Nguyen, H.; Rountrey, A.; Meeuwig, J.; Coulson, P.; Feng, M.; Newman, Stephen; Waite, A.; Wakefield, Corey; Meekan, M. (Nature Publishing Group, 2015)
© 2015, Macmillan Publishers Limited. All rights reserved.The effects of climate change on predatory fishes in deep shelf areas are difficult to predict because complex processes may govern food availability and temperature at depth. We characterised the net impact of recent environmental changes on hapuku (Polyprion oxygeneios), an apex predator found in continental slope habitats (>200 m depth) by using dendrochronology techniques to develop a multi-decadal record of growth from otoliths. Fish were sampled off temperate south-western Australia, a region strongly influenced by the Leeuwin Current, a poleward-flowing, eastern boundary current. The common variance among individual growth records was relatively low (3.4%), but the otolith chronology was positively correlated (r = 0.61, p < 0.02) with sea level at Fremantle, a proxy for the strength of the Leeuwin Current. The Leeuwin Current influences the primary productivity of shelf ecosystems, with a strong current favouring growth in hapuku. Leeuwin Current strength is predicted to decline under climate change models and this study provides evidence that associated productivity changes may flow through to higher trophic levels even in deep water habitats.